ISLAMIC ECONOMIC THOUGHT OF THE TIME OF RASULULLAH SAW AND KHULAFAURRASYIDIN: SOLU-TIONS AND CHALLENGES OF THE CONTEMPORARY TIME - Ramlah, Ramlah; Sapa, Nasrullah Bin; Lutfi, Mukhtar (The Pontianak State Institute of Islamic Studies, 2025)
This article examines Islamic economic thought during the time of Prophet Muhammad and the Khulafaur Rasyidin, which laid a significant foundation for Islamic economics. The study focuses on the relevance of Islamic economic concepts in addressing modern issues such as social inequality and economic exploitation. The research problem explores how early Islamic economic thought can provide solutions to current economic challenges. The study employs a literature review method, analyzing key Islamic principles such as zakat management, prohibition of usury, land distribution, and fiscal policies. Findings reveal that Islamic economic principles emphasize social justice and wealth distribution, offering viable solutions to contemporary economic problems. The article suggests integrating Islamic social justice principles into modern economic systems to reduce global economic inequality. In conclusion, the economic thought of the Prophet Muhammad and Khulafaur Rasyidin is highly relevant for building a more equitable and inclusive economic system.